2016
DOI: 10.7196/samj.2016.v106i5.9770
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence in early adolescence: The role of gender, socioeconomic factors and the school

Abstract: Background. Intimate partner violence (IPV) among adolescents is common worldwide, but our understanding of perpetration, gender differences and the role of social-ecological factors remains limited. Objectives. To explore the prevalence of physical and sexual IPV perpetration and victimisation by gender, and associated risk and protective factors. Methods. Young adolescents (N=2 839) from 41 randomly selected public high schools in the Western Cape region of South Africa (SA), participating in the PREPARE stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 11 publications
2
21
0
6
Order By: Relevance
“…Gender. The finding that male adolescents were more likely to endorse VAW than female adolescents is consistent with previous studies (Adika et al, 2013;Fakunmoju et al, 2016aFakunmoju et al, , 2016bMason-Jones et al, 2016;Pöllänen et al, 2018) and feminist theories that suggest that men are likely to uphold their patriarchal privilege, and support ideas and beliefs that reinforce this privilege (Igbelina-Igbokwe, 2013;Rani, Bonu, & Diop-Sidibe, 2004). Men and boys are unlikely to take responsibility for their poor behavior if social norms reinforce violent masculinities and provide men with excuses for perpetration of VAW.…”
Section: Effects Of Demographics On Beliefs About Vawsupporting
confidence: 86%
See 2 more Smart Citations
“…Gender. The finding that male adolescents were more likely to endorse VAW than female adolescents is consistent with previous studies (Adika et al, 2013;Fakunmoju et al, 2016aFakunmoju et al, , 2016bMason-Jones et al, 2016;Pöllänen et al, 2018) and feminist theories that suggest that men are likely to uphold their patriarchal privilege, and support ideas and beliefs that reinforce this privilege (Igbelina-Igbokwe, 2013;Rani, Bonu, & Diop-Sidibe, 2004). Men and boys are unlikely to take responsibility for their poor behavior if social norms reinforce violent masculinities and provide men with excuses for perpetration of VAW.…”
Section: Effects Of Demographics On Beliefs About Vawsupporting
confidence: 86%
“…Beyond its effects on perpetration of violence, exposure to violence has effects on adolescents' beliefs about VAW, primarily because exposure often underlies acceptance and perpetration of violence during adolescence and adulthood (Abrahams & Jewkes, 2005;Mueller et al, 2013). For example, on one hand, it was recently noted that exposure to and experience of sexual partner violence was associated with tolerance of sexual partner violence by both boys and girls (Mason-Jones et al, 2016;Pöllänen et al, 2018). Adolescents who were psychologically abused, on the other hand, were more likely to endorse domestic violence (Kunnuji, 2015).…”
Section: Correlates and Effects Of Exposure To Violence And Beliefs Amentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in South Africa, 40% of adolescent boys aged 15-19 years old report perpetrating sexual or physical IPV in the past year [15]. There is far less data on female perpetration, but what is available suggests that girls often perpetrate violence at rates similar to-or even greater than-boys [16][17][18][19][20]. A 32-country study, for example, found female university students were more likely to be physically violent towards their partner compared to male students [18].…”
Section: Introductionmentioning
confidence: 99%
“…En los Estados Unidos de Norteamérica; la violencia física durante el noviazgo entre los estudiantes osciló entre el 5,5% y el 12,1%(4). En Sudáfrica; el 19% de los adolescentes fueron víctimas/sobrevivientes de violencia de pareja y el 13% informaron que perpetraron violencia de pareja (5).…”
Section: Introductionunclassified